2019
DOI: 10.1111/jbi.13716
|View full text |Cite
|
Sign up to set email alerts
|

Exploring rain forest diversification using demographic model testing in the African foam‐nest treefrog Chiromantis rufescens

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 100 publications
8
49
0
Order By: Relevance
“…These species groups probably originated during the Miocene-Pliocene transition and subsequently during the Pliocene, when the African climate generally changed to drier conditions and oscillations between arid and humid conditions increased (Ruddiman, 1989). Our dating estimates generally match the dating of split events received for the afrobatrachian frogs (Portik et al, 2019) corresponding to the Miocene-Pliocene radiation of species groups and the Pleistocene age of closely related species pairs. A new lineage uncovered from the northern mountains of the CVL, named the P. arcanus species group, contains two new species from the Gotel Mts.…”
Section: Phylogeny Taxonomy and Biogeographysupporting
confidence: 70%
See 1 more Smart Citation
“…These species groups probably originated during the Miocene-Pliocene transition and subsequently during the Pliocene, when the African climate generally changed to drier conditions and oscillations between arid and humid conditions increased (Ruddiman, 1989). Our dating estimates generally match the dating of split events received for the afrobatrachian frogs (Portik et al, 2019) corresponding to the Miocene-Pliocene radiation of species groups and the Pleistocene age of closely related species pairs. A new lineage uncovered from the northern mountains of the CVL, named the P. arcanus species group, contains two new species from the Gotel Mts.…”
Section: Phylogeny Taxonomy and Biogeographysupporting
confidence: 70%
“…The identification of "P. hylaios" from Mt. Nlonako by Herrmann et al (2005) also remains questionable based on the biogeographic patterns (mountains north of the Sanaga River harbor usually different evolutionary lineages in amphibians; Portik et al, 2017;Charles et al, 2018;Leaché et al, 2019) until the specimen is thoroughly investigated. Last, "P. hylaios" on the photograph in Channing & Rödel (2019) also does not correspond to the morphology of P. hylaios (e.g., missing dark face mask).…”
Section: Phylogeny Taxonomy and Biogeographymentioning
confidence: 99%
“…Although initially these refugia were identified using species distributional patterns for birds and plants, an increasing number of recent studies have utilized molecular data to infer the geographical location of intraspecific diversity (i.e lineages or populations within species) across the Afrotropics. These studies have demonstrated contemporary phylogeographic patterns that suggest broadly concordant historical refugia in mammals (Bohoussou et al, 2015;Bryja, Mikula, Patzen, et al, 2014;Bryja, Mikula, Šumbera, et al, 2014;Bryja et al, 2017;Gaubert et al, 2016;Mizerovská et al, 2019;Nicolas et al, 2011), including other primates, (Anthony et al, 2014;Clifford et al, 2004;Gonder et al, 2011;Pozzi, 2016;Telfer et al, 2003), amphibians (Charles et al, 2018Leaché et al, 2019;Portik et al, 2017), and plants (Faye et al, 2016;Hardy et al, 2013;Piñeiro, Dauby, Kaymak, & Hardy, 2017;Piñeiro et al, 2019), albeit with some differences between species due to different ecological characteristics and idiosyncratic responses to climatic changes (Lowe, Harris, Dormontt, & Dawson, 2010).…”
Section: Understanding Historical and Recent Factors Shaping Contempomentioning
confidence: 99%
“…for a large number of wild chimpanzee populations. Rapid developments in the generation and analysis of genomewide molecular data over the past decade have revealed detailed demographic histories, enabling the identification of diversification mechanisms due to forest refugia, which are characterised by divergence, isolation, and secondary contact as refugial habitats fragment and reconnect with each other during glacial cycles (Barratt et al 2018;Charles et al, 2018;Leaché et al, 2019;Portik et al, 2017, Feng, Ruhsam, Wang, Li & Wang, in press). The ability to distinguish signals of forest refugia from other diversification mechanisms such as landscape barriers, ecological gradients, and anthropogenic habitat fragmentation, would represent a powerful approach for gaining a more mechanistic understanding of population diversification.…”
Section: Future Directions For Understanding Diversification Mechanismsmentioning
confidence: 99%
“…2018; Leaché et al. 2019a). Determining whether these population divergence events are temporally congruent with recent Holocene climate change or with older biogeographic events requires a comparative study of the genealogical divergence among populations in these communities.…”
mentioning
confidence: 99%